(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out during the 2021- 2022 agricultural season to study the effect of treatment with the chemical mutagen Ethyl Methane Sulfonate (EMS) in improving the tolerance of two tobacco cultivars (Burley 21 and Virginia VK51) to drought stress. The seeds were treated using three concentrations of the mutagen (0, 0.1, 0.5 and 1 %) with a soaking time of ( hours. In addition, to induce drought stress, polyethylene glycol (PEG) was used at concentrations (15, 30 and 45 %) equivalent to an osmotic pressure (-0.52, -1.04 and -1.56) MPa. The experiment was conducted according to a randomized complete block design (RCBD) at the Damsarkho farm of- Lattakia- Syria, and with three replications per treatment. Some biochemical (chlorophyll and carotenoids contents (µg/g FW), proline content (µg/g FW) and H2O2 content) were measured. The treatment with PEG at the high concentration, conducted to negative effects on chlorophyll and carotenoids, proline and H2O2 content of two tobacco varieties.Treatment with EMS at a low concentration (0.1) % led to an increase in the chlorophyll and carotenoids contents, and decrease in the proline and H2O2 content of two tobacco varieties (Berley 21 and Virginia VK51). while the high concentration of EMS at 0,5 and 1 % caused a decrease in the chlorophyll and carotenoids content, and increase in the proline and H2O2 content of two tobacco varieties (Berley 21 and Virginia VK51). The chemical mutagen treatment under drought stress conditions at a low concentration (0.1) %, also improved the values of most of the studied indicators compared to the other treatments. Thus, it can be suggested to soak the seeds at the concentration 0.1% for its role in improving the biochemical traits of two tobacco varieties (Berley 21 and Virginia VK51).